The The Relationship Between Lung Quality and Anxiety Levels in Patients with Post-Tuberculosis Obstructive Syndrome - Rahman, Ahmad Farghani; Sadmita, Salki; Hasyar, Andi Rizky Arbaim; Kadir, Irianto (Physiotherapy, Exercise, and Rehabilitation Sciences Journal, 2026)
Aims: This study aims to examine whether there is a relationship between lung quality and anxiety levels in SOPT patients at the Makassar Lung Health Center. Methods: This research is a quantitative study with a descriptive analytical design using a cross- sectional approach. Subjects were selected using an accidental sampling technique. Results: The results of this study obtained 60 respondents and obtained average lung quality results for spirometry 5.07 and Borg scale 7.85, for anxiety level 4.07, and Spearman test results obtained spirometry results to HARS (0.004) and Borg scale to HARS (0.001). Conclusion: There is a moderately weak positive significant relationship between lung quality and anxiety levels in SOPT patients at BBKPM.